Tinjauan Indikator-indikator Pemenuhan Klaim dalam Proses Klaim Asuransi Jiwa pada PT. Prudential Life Assurance Syariah Cabang Binjai Kota - Widia Angraini; Nur Ahmadi Bi Rahmani; Wahyu Syarvina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the indicators of claim fulfillment of the Life Insurance claim process at PT Prudential Life Insurance Syariah Binjai City Branch and to find out the causes of life insurance claims can be delayed or rejected at PT Pruential Life Isurance Binjai City Branch... The research used is descriptive qualitative. The results showed that in general there are four claim processes including claim notification, proof of claim documents, claim investigation and claim settlement. The four claim processes implemented by PT Prudential Life Assurance Syariah are quite simple and easy. The cause of the delayed claim is the lack of documents provided by the institution on behalf of the participants to the insurance company so that the claim is postponed until the file is completed at a predetermined time. The causes of rejected claims are as follows Customer dishonesty, Exclusion by the insurance company in paying the sum insured, The customer takes too long to submit a claim, The requirements when submitting a claim are incomplete, Non-payment of premiums by customers within a predetermined period. The cause of the delayed claim is the lack of documents provided by the institution on behalf of the participants to the insurance so that the claim is postponed until the file is completed at a predetermined time.